2000
DOI: 10.1007/s007020070006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging distinguishes progressive supranuclear palsy from multiple system atrophy

Abstract: To establish diagnostic magnetic resonance imaging (MRI) criteria for differentiating progressive supranuclear palsy (PSP) from multiple system atrophy (MSA), magnetic resonance images from eight patients with probable PSP, 30 with probable MSA (nine striatonigral degeneration (MSA-P) and 21 olivopontocerebellar atrophy (MSA-C)), and ten age-matched controls were retrospectively studied. Anteroposterior diameters in the midline sagittal T1-weighted image of the rostral (RMT) and caudal midbrain tegmentum (CMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…Recent MRÎ ndings of parkinsonian syndromes have indicated that a low midbrain diameter may be valuable in discriminating PSP from Parkinson's disease and MSA. 6,7 However, the values overlap with those of the latter disorders. 6,7 We retrospectively reviewed MRIˆndings obtained from patients with Parkinson's disease, PSP, and MSA in order to investigate the morphological characteristics of the midbrain in parkinsonian syndromes.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recent MRÎ ndings of parkinsonian syndromes have indicated that a low midbrain diameter may be valuable in discriminating PSP from Parkinson's disease and MSA. 6,7 However, the values overlap with those of the latter disorders. 6,7 We retrospectively reviewed MRIˆndings obtained from patients with Parkinson's disease, PSP, and MSA in order to investigate the morphological characteristics of the midbrain in parkinsonian syndromes.…”
Section: Discussionmentioning
confidence: 88%
“…6,7 However, the values overlap with those of the latter disorders. 6,7 We retrospectively reviewed MRIˆndings obtained from patients with Parkinson's disease, PSP, and MSA in order to investigate the morphological characteristics of the midbrain in parkinsonian syndromes. A peculiar atrophy of the midbrain has been seen in patients with PSP and MSA who had progressive supranuclear gaze-palsy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For instance, in Parkinson's disease, diagnosis can frequently be assumed on clinical basis only and the overall ability for routine MRI to differentiate patients with PD from controls is modest. Thus, the major relevance of certain MRI findings is to discriminate among other parkinsonian disorders [14][15][16] . Other relevant consideration is the fact that the linear and morphometric measures employed here can be easily performed.…”
Section: Discussionmentioning
confidence: 99%
“…The mid-sagittal image of the T1-weighted SE sequence was used for measurements of the midbrain area (Ams) and pons area (Apn) [12][13][14] (Fig 1). These areas were obtained according to the following parameters: two straight lines were drawn.…”
Section: Methodsmentioning
confidence: 99%